Primaquine in vivax malaria: an update and review on management issues - Fernando Deepika; Rodrigo Chaturaka; Rajapakse Senaka (Malaria Journal, 2011)
Abstract Primaquine was officially licensed as an anti-malarial drug by the FDA in 1952. It has remained the only FDA licensed drug capable of clearing the intra-hepatic schizonts and hypnozoites of Plasmodium vivax . This update and review focuses on five major aspects of primaquine use in treatment of vivax malaria, namely: a) evidence of efficacy of primaquine for its current indications; b) potential hazards of its widespread use, c) critical analysis of reported resistance against primaquine containing regimens; d) evidence for combining primaquine with artemisinins in areas of chloroquine resistance; and e) the potential for replacement of primaquine with newer drugs.